PRONOUNCIATION QUALITY OF JAVANESE OF ESL STUDENTS IN PRODUCING THE ENGSLSH SOUND: A CASE STUDY OF JAVANESE ESL STUDENTS IN TERITARY LEVEL - Malikatul Laila (Universitas Sebelas Maret, 2012)
The quality of pronouncing English sounds by Javanese ESL students is much influenced by their way of speaking of their native language. The study aims to examine how Javanese ESL students shift their articulation in producing the English sounds. The data are Javanese ESL students’ speech of English in the forms of words, phrases, and sentences which are collected by means of recording, testing and participant interview. The data analysis applies techniques of comparison and contrast _between RP and Javanese ESL sounds_ in the domain of impressionistic articulatory phonetics which is assisted by using Audio Edit Magic (AEM). The result shows that Javanese ESL students produce consonant sounds by the lack of maximal force and tend to be lenis; while in pronouncing vowel sounds, they tend to produce some as its phonemes. This shifts the NSE/ FSE have perceived intelligibly is 53,8 %. This implies that Javanese ESL students’ shift in pronouncing the English sounds represented in words is still perceived and understood properly by the NSE/ FSE.Key words: pronunciation quality, shift, intelligibility, RP, and impressionistic articulatory phonetics.